Electrochemistry of 4-[(4-aminobenzene) sulfonyl] phenylamine - Silio Lima de Moura (2015)
This work provides a new insight on the oxidation mechanism of 4-[(4-aminobenzene) sulfonyl] phenylamine, commonly known as Dapsone. The dapsone oxidation mechanism was investigated by electrochemical, spectroscopic and spectrometric techniques and quantum chemical calculations. Cyclic voltammetry studies showed well-defined oxidation peaks at aqueous and nonaqueous media. In order to establish the electrochemical kinetic laws, voltammograms of dapsone were carried out under different experimental conditions. Electrochemical impedance spectroscopy was applied to the investigation of electrochemical properties of adsorbed dapsone. By controlled potential coulometry the number of electron in overall electrochemical reactions was determined, and quantum chemical calculations revealed that the amino and sulfone moiety of the molecule are involved in the electronic transitions. The equilibrium geometry and vibrational spectra were calculated by using DFT (B3LYP, M06 and M062X) with 6-311+G* and 6-31+G(d,p) basis set. TD-DFT of the electronic spectra of dapsone was reported for the first time demonstrating that the protonation has a very important role in the excited states. The electropolymerization of dapsone by anodic oxidation is reported for the first time. The conditions in which a blocking oligomeric film or a conductive polymeric film of dapsone is formed are also discussed, based on the potential window applied. The cyclic voltammetry of polydapsone presented redox activities, demonstrating its high electronic conductivity. Infrared spectroscopy of both oligomers and polymer supports that the polymerization occurs via amino-amino coupling, since no modifications in the aromatic ring is observed. In addition, preliminary corrosion protection test of the aluminum covered with chemically synthetized polydapsone indicates that it can be used to coating against corrosion. A model for mechanism of corrosion control is proposed.